Pesticide Residues Impact on Drinking Water and Farmers Using Environmental Health Risk Assessment Study (EHRA) - Glenzi Fizulmi; Bambang Wispriyono (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Public health problems and decreased environmental health can be caused by pesticides because they are dangerous toxic substances. Pesticides have had a risky impact on farmers in Jonggol village. Assessing the risk of pesticide exposure to drinking water sources in agricultural areas in Jonggol village in 2022 is the aim of this study. The research used the Environmental Health Risk Assessment study. Conducting interviews with questionnaires, measuring pesticides in drinking water sources, and observing are part of the research data collection. The results of research conducted at 3 points only found pesticides at the first point, namely in the well water in Kampung Kujang with a value above the standard of 0.0855 mg/l the location is only 2 m from the agriculture. In the next two points, namely well water in Karni village and river water in Bengkok village, no pesticides were detected and the distance from the agriculture was 20 m. Most of the water from wells in agricultural areas is consumed by farmers for drinking. The calculation result was 0.00246 mg/kg/day for non-carcinogenic intake values (real-time) and 0.001056 mg/kg/day for carcinogenic intake values (real-time). The results showed there was no non-carcinogenic risk with RQ value of ≤ 1 with a value of characteristics of non-carcinogenic risk was 0.246. The conclusion is that both in real-time and in a lifetime, farmers in Jonggol village are already at risk. The risk of health problems for farmers can be reduced by the importance of protecting farmers by carrying out risk management.